A Study of Education History on Gifted Children: Research on Their Learning Achievement as They Started Their School Under Seven - Dimyati, Johni (EDUCARE, 2015)
ABSTRACT: A child with a high intelligence or a talented child was deemed able to distinguish between behaviors and to have a high learning ability. In contrast, another child having a low intelligence would always fail in all areas. This conventional view believed that intelligence is an ability that can be used to solve all problems in life. Among Indonesian society, especially among those involved in the basic education, there is a questionable belief that when a young child of less than 7 years starts to enroll a primary school he/she cannot study well. Based on the theoretical frame, this research proposes a hypotheses: âA gifted child does not experience any problem of academic achievement and the disorders of mental hectic and brain fatigue when he/she starts the primary school before sevenâ. This is a longitudinal study using documentation and observation for the data collection. The observation carried out by following the educational experience of the subjects studied in a fairly long period of time. Three subjects were studied. All of them started their elementary education under sever years old. They joined kindergarten under 5 years, and one of them even started his experience of learning when he was still so young, 3-year-old. The method of analysis data used a qualitative descriptive. The research results prove that the hypothesis proposed is accepted or proven, meaning that gifted children starting their elementary school before seven will not have problems in the academic achievement and do not suffer the disorders of mental hectic and brain fatigue, provided they are given education appropriate to their talents.KEY WORDS: Longitudinal study, gifted children, intelligence, elementary education under sever years, and not have problems in the academic achievement.About the Author: Johni Dimyati is a Senior Lecturer at the Faculty of Letters UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto City, Central Java, Indonesia. For academic purposes, the author can be contacted via mobile phone at: +6285643534732 or via e-mail at: kristian.topz@gmail.comHow to cite this article? Dimyati, Johni. (2015). âA Study of Education History on Gifted Children: Research on Their Learning Achievement as They Started Their School Under Sevenâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, pp.45-54. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (July 3, 2015); Revised (August 3, 2015); and Published (August 25, 2015).